Formation of Football Talents in the Education System of Germany - Volodymyr Naumchuk; Andriy Ohnystyy; Kateryna Ohnysta; Viktor Shandryhos; Andriy Ivehesh; Oleksandr Motychko (JUMORA: Jurnal Moderasi Olahraga, 2023)
The purpose of this study is to examine the key aspects of the talent development process in youth football within the educational system of Germany. Germany is renowned for its high educational standards and remarkable achievements of its athletes on the international stage. In order to accomplish this objective, a comprehensive set of interconnected methods, including analysis, synthesis, and generalization of scientific information pertaining to the specific issue, as well as educational and methodological literature and internet sources, were employed. The study reveals that a successful football career is the outcome of the interaction between two pedagogical systems: one that reflects an individual's educational endeavors and the other which relates to their sporting accomplishments. The step-by-step construction of the educational and sports systems, their common orientation, which enables constant multifaceted control and support of each young talent, optimally coordinates all areas of his life, promotes further harmonious development. It has been proven that the German model provides comprehensive support of the chosen professional path, the opportunity to study in the institutions that correspond to the preferences, aspirations and abilities of the individual. Keywords: Education system, sports training, football, young talents